Utilization Possibility of Cacao Fruit Shell (Theobroma cacao, L) as A Source of Natural Pigment (ï¢- Carotene) - Wulan, Siti Narsito (Jurnal Teknologi Pertanian, 2001)
The possibility to utilize cacao fruit shell as a source of natural pigment was studied. The study included quantitative and qualitative aspects. Quantitative analysis to determine the optimum condition of pigment extraction was done by varying the materials (fresh and dried cacao fruit shell), the concentrations of ethanol as a solvent (75%, 85% and 95%) and the ratios between cacao fruit shell and ethanol (1:1, 1:2, and 1:3). The highest concentration pigment extract (as mg b carotene/g material) was given by these conditions: fresh cacao fruit shell, ethanol concentration 95% and the ratio 1:3. Qualitative analysis to determine the heat stability of the pigment extract was done by heat treatment in vary temperatures and time exposures (70°C, 80°C, 90°C and 100°C for 15, 30, 45 and 60 minutes). Pigment degradation was detected by measuring the absorbance in l 435 nm with spectrophotometer analysis. Pigment degradation was detected in all temperatures during 30 minutes heat treatment. Pigment was also unstable in acid and basic conditions (pH 3, 4, 5, 8 and 9) but stable in neutral condition (pH 7). Degradation was occurred when H2O2 (oxidator) and Na2S2O3 (reductor) were added to the pigment extract. Keywords: cacao fruit shell, natural pigment, b- Carotene